Geo-resource mapping in the Lakhssas plateau and Ifni massif, Morocco: a geomatics and geotechnical perspective - Mahmoud Sebbab, Mohamed; El Ouahidi, Abdelhadi; Atik, Mohamed; Taghlaoui, Hamza; El Atillah, Abdessamad; Ousbih, Mehdi; Sebbab, Khadija (Revista de Estudios Andaluces, 2025)
A comprehensive geo-resource assessment of the Lakhssas plateau and Ifni massif was undertaken to optimize quarry siting. The methodology employed involved geomechanical characterization of rock outcrops, coupled with spatial analysis using a Geographic Information System (GIS). Representative sampling was used to conduct geotechnical tests in the laboratory. Results were classified according to standards (Moroccan and European). Integration of these data within the GIS yielded a geotechnical map delineating five classes of exploitation potential: High, Medium, Low, Very Low, and None. Spatial analysis revealed that approximately 72% of the study area exhibits high potential. This integrated field– and GIS-based approach provides a robust decision-support tool for sustainable management of extractive resources and preservation of geological heritage, establishing a rigorous methodological framework for responsible development of the quarrying sector.